Fabrication of magnetic core shell particles coated with phenylalanine imprinted polymer. (May 2019) - Gul, Saba; Shah, Nasrullah; Arain, Muhammad Balal; Rahman, Nida; Rehan, Touseef; Ul-Islam, Mazhar; Ullah, Muhammad Wajid; Yang, Guang
Abstract: In this study, magnetic iron oxide (Fe3 O4 ) nanoparticles with excellent magnetic behavior were synthesized by co-precipitation method followed by their surface modification to obtain Fe3 O4 @SiO2 NH2 and polymerization to fabricate d -phenylalanine (D-Phe) imprinted magnetic core-shell polymer (PIMP) and non-imprinted magnetic core-shell polymer (NIMP), respectively. The as-prepared PIMP and NIMP were characterized by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction analysis (XRD), and energy-dispersive X-ray spectroscopy (EDX). PIMP showed maximum adsorption capacity (3.94 mg. g −1 ) and selectivity factor (1.55) at pH 4 while the adsorption equilibrium was achieved after 1 h. The adsorption of Phe on PIMP followed Langmuir adsorption isotherm with pseudo second order kinetics. PIMP was selective towards template (D-Phe) in the presence of interfering molecules such as L-Phe, tyrosine, and tryptophan. It was concluded that the as-synthesized PIMP is an important material to be used as a recoverable selective adsorbent and sensor for Phe. Highlights: Fabrication of Phe imprinted magnetic core-shell particles (PIMPs) by ultrasonic assisted precipitation polymerization. Langmuir adsorption isotherm and kinetic analysis of PIMPs. Excellent magnetic behavior, high adsorption capacity, selectivity, and specificity of PIMPs.